Chilocoris laevicollis Horváth, 1919, and Ch. umbricola Linnavuori, 1993—two trogloxenic burrower bugs recorded for the first time in Gabon (Central Africa) - Lis, Barbara; Lis, Jerzy A. (Zootaxa, 2016)
First country records of two burrower bugs, Chilocoris laevicollis, and Ch. umbricola (Hemiptera: Heteroptera: Cydnidae) from Gabon (Central Africa) are presented. The study was based on the specimens collected by Dr. V. Aellen, a well-known Swiss speleologist, taken from two caves near Lastoursville in the Gabonese Republic. Diagnostic characters for both recorded species are provided, and data on their biology and distribution are summarized.